KESADARAN HUKUM PEMILIK KENDARAAN PLAT HITAM DALAM MEMANFAATKAN KENDARAAN SEBAGAI ANGKUTAN PENUMPANG - NIM. A1011161290, GEO DESTIAN WICAKSONO (Fakultas Hukum Universitas Tanjungpura, 2023)
ABSTRACTThis thesis is entitled: Legal Awareness of Black Plate Vehicle Owners in Utilizing Vehicles as Passenger Transportation. The formulation of the problem in this thesis research is: